The Z Factor: My Journey as the Wrong Man at the Right Time - Chandra, Subhash; Sharma, Pranjal; Mittal, A.K. (Gyan Management Journal, 2016)
The story is about a person who had a vision to change the world. His dedication, hard work and the hunger to succeed helped him reach the position he is on today. Dr Sub hash Chandra gives a detailed account of what it took for him to reach where he is today. The Z Factor is the book that imparts the courageous and bold attitude of Dr. Subhash Chandra to dream of becoming a billionaire one day.The -life events, persons he met, struggles & his transformation to what he is are the reasons for which the book can't be missed out and acts as the motivational one for budding entrepreneurs. Every page had that impact! This autobiography is his ingredients of success with all moments of his life perfectly described.
Keywords: world; vision; dedication; hard work; hunger; entrepreneurs; autobiography